INVESTIGATING CONTROLLED GRAIN GRAVITATIONAL MOVEMENT IN SLOPING CHANNEL WITH THREE VARIABLE ANGLES - Antonets, A. V.; Flegantov, L. O.; Ivanov, O. M.; Arendarenko, V. M.; Koshova, O. P. (Scientific Progress & Innovations, 2021)
Food security of countries depends on grain quality. Special devices are used to prevent the injury of grain mass during its transportation and loading. They can work on the principle of overflow, current, and with the use of gravitational braking devices. In gravitational devices, it is important to solve the problem of controlled reducing grain speed and prevent its untimely unloading. The aim of this paper was to find the relationship between the angles of one acceleration and two brake sections of gravitational unit to obtain the controlled initial grain speed at its exit. The main task was to find and substantiate the relationship between the three angles of one acceleration and two brake sections. The experimental gravitational installation was proposed to study the angles and grain speed. It has an acceleration section located at an angle α to the horizon, where the grain flow has its maximum speed Vmax passing the way of length l1. On the first brake section with angle β and length l2 , the grain slows down its movement to the average value between the maximum and final speeds. At the end of the second brake section with an angle γ and length l3, the grain speed becomes close to the initial grain speed V0 as a result of falling from the height h0 of the hopper to the beginning of the acceleration section. To ensure the controlled speed of grain movement, mathematical correlations between the slope angles of acceleration and braking sections of the gravitation device were found. The analysis of the nature of changing slope angles of brake channels at changing the determining factors forming their sizes was carried out. The ratios between the angles α, β and γ were primarily deter-mined by the value of the coefficient µ of friction-sliding, which depends on the type of grain, its humidity level and roughness of the tray material of the gravitational loading device. The lengths of sections l1, l2 and l3 also significantly affect the correlation between the slope angles, as well as the shape of the proposed gravitational installation.